LONG-TERM USE OF INHALED HYPERTONIC SALINE IN CHILDREN AND ADOLESCENTS WITH CYSTIC FIBROSIS: EXPERIENCE FROM A TERTIARY CARE CENTER IN A LOW AND MIDDLE INCOME COUNTRY - Abdul Aziz, Danish; shahid, Shahira; Alam, Anusha; Aziz, Namrah; Mir, Fatima (Journal of Ayub Medical College Abbottabad, 2022)
Background Long term hypertonic saline use has been found to improve mucus transport, airway hydration, and mucociliary clearance in patients with cystic fibrosis. However, the effect of hypertonic saline on the outcomes of patients with cystic fibrosis is not well established. The aim of our study was to determine the long-term use of hypertonic saline in reducing pulmonary exacerbations, length of hospital stay and pseudomonas colonization in patients with cystic fibrosis admitted for treatment at a tertiary care referral center. Methods: Retrospective cohort study was conducted on 71 patients with cystic fibrosis. Patients ranged in age between 3-18 years. All patients with two to five pulmonary exacerbations in the preceding six months were included in the study. Those who received regular inhaled 3-7% hypertonic saline twice daily during their admission and till 6 months after discharge from hospital were categorized as hypertonic saline (HTS) group. Patients who did not receive regular hypertonic saline for 6 months were included in the non-hypertonic saline (NHTS) group. Data was analyzed at the end of one year. Results: The HTS group had 37 patients whereas, the NHTS group had 34 patients. Mean number of exacerbation episodes was significantly lower in HTS group (2.18±0.84) as compared to NHTS group (3.67±0.91) (p<0.01) whereas, length of hospital stays and frequency of pseudomonas colonization did not significantly differ between the two groups (p=0.78 and p=0.12 respectively). The mean number of pulmonary exacerbations also significantly reduced from 3.11±1.07 to 2.18±0.84 p-value <0.01 in the HTS group over the follow-up period of one year. Conclusion: Long term hypertonic saline therapy is beneficial in patients with cystic fibrosis in preventing pulmonary exacerbations and subsequently reducing morbidity.